Palatability and the Micro-structure of Feeding in Humans: the Appetizer Effect - YEOMANS, MARTIN R. (Appetite, 1996)
The effects of manipulated palatability on eating were assessed in 54 human volunteers eating pasta with a tomato sauce, with palatability adjusted by the addition of three levels of oregano. Meals were divided into 2 min eating episodes separated by brief pauses during which subjects rated aspects of appetite. Both intake and eating rate were greatest in the most palatable condition (0·27% oregano), whereas the addition of 0·54% reduced intake and eating rate. Hunger ratings increased during the initial stages of the meal with 0·27% oregano, but fell throughout the meal in the other conditions, whereas fullness ratings increased similarly in all three conditions. Rated food attractiveness was greatest with 0·27% oregano, and least with 0·54% oregano, but declined similarly through the meal with all three foods. Initial ratings of palatability were similar to those for food attractiveness, but changes in palatability across meals varied between subjects. Male subjects consistently ate more and faster than females, but similar effects of manipulated palatability on intake and subjective appetite were seen in both sexes. These data are consistent with the idea that palatability increases intake through a positive-feedback reward mechanism, and offers a novel method for measuring these effects.